TANGGUNGJAWAB PENGURUS LPD DALAM PENGELOLAAN KEUANGAN DESA PAKRAMAN - Rama Darmawangsa, I Gusti Ngurah; Mertha, I Ketut; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017), 2017)
One of the non-bank financial institutions in Indonesia, especially in Bali is the Village Credit Institutions (LPD). As a non-bank financial institutions, the different LPD system implemented by the banking system in general, which tends to prioritize its activities to pursue distinct profit entity with LPD more mengutakan the interests and welfare of the community by providing a wide range of easiness. Along with the development and existence are increasingly being recognized and trusted by the public, then there is also improvement of its regulation of LPD that until today has undergone improvements to the issuance of Bali Provincial Regulation No. 3 of 2007 on Credit Institutions Desa (LPD). From this background, this thesis research moved from the management arrangements and accountability form LPD relating to the financial management of the Pakraman and customers. This study uses normative law research with the consideration that the starting point of the research is the analysis of the norm vague in terms of monitoring the implementation of the LPD, the approach used to address the problem is the approach of legislation, the conceptual approach and the approach to history while the legal materials used are legal materials legislation and analysis used is the analysis of grammatical interpretation, interpretation of systematic and historical interpretation that subsequent analysis based on relevant theories. The results of this study came to the conclusion that the management arrangements end of the financial Pakraman conducted by LPD, by adhering to the precautionary principle in order to LPD remain healthy, with provision concerns such as: capital adequacy, lending limits, the system klasivikasi loans, provision of spare borrowing hesitation (CPRR) sufficient, liquidity management, work plan and budget plan revenue expenditure (RK-RAPB) LPD and reports. LPD form of accountability in financial management and customer Pakraman where the board to submit a report on the activities, developments and liquidity LPD regularly every month and report every three months to the level of supervisor, BPD, PLPDK, and prajuru village.